The neoliberalization of higher education in England: An alternative is possible*. (June 2017) - Maisuria, Alpesh; Cole, Mike
In this article, we provide a critical explanation and critique of neoliberalism. We attempt an innovative focus ranging from the wider contemporary political and ideological shifts, to the way in which neoliberal policy specifically influences higher education and the consequences thereof. We follow a narrative logic in three parts where we first explore the bigger picture, then concentrate on specific examples, finally taking a long-term perspective with regard to class struggle. In the first part, we lay out neoliberalism and explicate its basic principles in abstraction. This is necessary for part two, where we contextualize neoliberalism specifically within the English higher education system with specific reference to the policy agenda of successive governments since 1979. In the third and final part of the article we suggest an alternative higher education model that simultaneously exists and flourishes along with and against the neoliberal hegemony. We conclude by suggesting the strengthening possibility of class formation and struggle in this moment of history when neoliberalism is expanding and deepening.